(untitled) (Світ фінансів, 2017)
Кнейслер О. В., Маринчак Л. Р. Інновації як вектор розвитку та модернізації депозитної діяльності банківських установ. Обґрунтовано доцільність впровадження інновацій у депозитній діяльності банків у контексті удосконалення асортименту депозитних продуктів і послуг, підвищення якості депозитного обслуговування відповідно до зростаючого попиту клієнтів. Розкрито роль банківського маркетингу та виокремлено основні блоки його функцій, орієнтованих на інноваційний розвиток банківської установи. Відображено авторську позицію щодо градації клієнтської бази та інноваційних кроків менеджменту банку в розвитку депозитної діяльності. Запропоновано градацію споживачів депозитних банківських продуктів на категорії відповідно до способу життя, що забезпечить урахування пріоритетів наявних і потенційних клієнтів банку, їх уподобань та рівня відкритості до сприйняття інновацій. Кнейслер О. В., Марынчак Л. Р. Инновации как вектор развития и модернизации депозитной деятельности банковских учреждений. Обоснована целесообразность внедрения в депозитной деятельности банков ин новаций в контексте усовершенствования ассортимента депозитных продуктов и услуг, повышения качества депозитного обслуживания в соответствии с растущим спросом клиентов. Раскрыта роль банковского маркетинга и выделены основные блоки его функций, ориентированных на инновационное развитие банковского учреждения. Отражена авторская позиция относительно градации клиентской базы и инновационных шагов менеджмента банка в развитии депозитной деятельности. Предложено градацию потребителей депозитных банковских продуктов на категории в соответствии с образом жизни с учетом приоритетов имеющихся и потенциальных клиентов банка, их предпочтений и уровня открытости к восприятию инноваций. Kneysler O., Marynchak L. Innovations as vector of development and modernization of deposit activities of banking institutions. Introduction. The expediency of introduction of innovations into deposit banking activities in the context of improving the range of deposit products and services, improving the quality deposit services in accordance with the growing demand of customers are substantiated. The role of bank marketing is revealed, the function of which is the coordination of commodity, price, distribution and communication policy of the bank. Purpose. The main blocks of marketing functions are outlined, focused on innovative development of banking institution, namely: work with the environment, which is based on innovative technologies of socio-economic monitoring; sales organization, which is based on innovations the work with customers and includes different features of attracting and retaining the customers; advertising (communication policy), that is characterized by innovative product policy of the bank; organization of marketing activities of the bank, which is directly related to staff training that can develop innovations, innovation planning of innovation activities, budgeting and so on. The necessity of consideration of several key stages of new banking products and services used in the global banking sector is proved. Results. The author’s position on the graduation of customer base and innovative steps of the bank management into the development of deposit activities is showed. The gradation of consumers of deposit banking products into the categories according to the way of life is suggested, that will contribute to a better understanding of client positions on the choice of a product. Conclusion. The developed model of adaptation of the deposit bank program to the way of client’s life will provide the consideration of priorities of existing and potential bank customers, their preferences and the openness level to accept the innovations and will help to create an optimal deposit offer.